Teaching case: A man with a progressive gait impairment and visual compromise (2015)
Primary progressive multiple sclerosis can present with a wide variety of symptoms. We report a case of a 52-year-old man presenting with visual symptoms and gait impairment in whom a diagnosis of a primary progressive multiple sclerosis was established. Symptomatic treatment with dalfampridine was started but did not result in a considerable improvement. Gait disorders in multiple sclerosis are common and can have a considerable effect over the patient׳s quality of life. Dalfampridine is the first drug approved for the symptomatic treatment of gait in MS, although only a 40% of patients show an objective response to this medication. Primary progressive multiple sclerosis represents a therapeutic challenge. Currently, there are no disease modifying treatments approved but there are several medications undergoing assessment for this indication. Further research in the underlying pathophysiology of PPMS will help us develope more successful disease-modifying treatments. Meanwhile, a symptomatic approach should be offered in order to improve the patient׳s quality of life.